Correlation Analysis of Gross Regional Product and Industries of Regional Economy - M. V. Dubovik; S. G. Dmitriev (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The article carried out correlation analysis of gross regional product and figures of regional economy industries, including analysis of correlation with the time lag. The authors found out that there is a correlation between separate industries of regional economy and gross regional product, however, it is not statistically important for the majority of indicators. The Granger causation test did not show a stable interconnection between the said indicators either. According to the authors, the mentioned correlation can be explained by the Geks – Krevosier matrix. A conclusion was drawn that in the current situation caused by different factors, including COVID-19 pandemic, it is more reasonable to re-orient regional economy to local people needs and the development of service sectors. Disclosed low rates of convergence in regions, which are members of the Central Federal Area of Russia, can be useful for reorientation of macro-economic policy to partial autonomization of regional economy.